360 degree vision based sensor network for multi-target tracking - Chan, Alvin Han Shen. (2010)
In this report, the author explores the utilization of a single IP camera to provide a Omni-directional image of the environment for real time tracking and survillance of an area. The Omni-directional camera system comprises of an internet protocol camera and a conical mirror. It produces circular 360° images which need to be un-warped to rectangular panoramic images These are built on the platform of Java, Matlab and C++ programming. Image retrieval from the IP camera is coded using Java; the program automatically grabs and updates images from the IP address of the IP Camera. Matlab Programming is also utilized to unwarp the 360° image. Image Processing and Target Tracking is coded in C++, with the inclusive of OpenCV( a Open Source Computer Vision Library).